PENGARUH KUALITAS PELAYANAN ZAKAT TERHADAP KEPUASAN MUZAKKI DI BAZNAS KOTA TASIKMALAYA (Studi Kasus Pada Muzakki di Baznas Kota Tasikmalaya) - Fauzy Ridwan, Irwan (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2024)
The purpose of this study was to analyze and find out how much zakat service quality and how big the level of muzakki satisfaction towards BAZNAS Tasikmlaya City and to determine whether or not there is a relationship between zakat service quality and Muzakki satisfaction carried out by BAZNAS Tasikmalaya City. This study used primary data collection techniques carried out by survey methods with a quantitative approach. The analytical method used is Simple Linear Regression Analysis. In this study, to test the hypothetical relationship, data processing was carried out using SPSS Statistics version 24 software. Based on the results of data analysis using SPSS Statistics version 24 Software, it is known that the quality of zakat services in the City of Tasikmalaya needs special attention because the services provided by BAZNAS in the City of Tasimalaya are not optimal. It can be seen from the data distributed, there are some who do not feel and are not satisfied with the quality of service provided by the Tasikmalaya City BAZAS. The satisfaction of muzakki with BAZNAS Tasikmalaya City can be said to be quite satisfied based on a questionnaire conducted to a number of muzakki, but there are still those who are not satisfied with the performance of BAZNAS Tasikmalaya City. The direct effect of service quality on muzakki satisfaction, based on the statistical calculation of the t-test, the t-count value was -0.030 with a significance value of 0.976 greater than 0.05 (0.976> 0.05) and the regression coefficient had a negative value of -0.006. Thus the quality of service does not significantly affect the satisfaction of muzakki. The coefficient value between service quality variables and muzakki satisfaction at BAZNAS Tasikmalaya City which was formed resulted in a negative relationship. With a correlation result of -0.006, this shows that the quality of service provided by BAZNAS Tasikmalaya City is still far from expectations and cannot be felt by muzakki at BAZNAS Tasikmalaya City or it can be said that the quality of service is still very low.